Theaflavin Reduces Oxidative Stress and Apoptosis in Oxidized Protein-Induced Granulosa Cells and Improves Production Performance in Laying Hens - Ling Zhou; Li Lv; Pinyao Zhao; Jinwei Zhang; Yan Liu; Wei Zhao; Keying Zhang; Shuwen Du (Animals)
This study aims to investigate the effects of theaflavins on production performance and egg quality in laying hens fed oxidized corn gluten meal while evaluating their antioxidant and anti-apoptotic effects on granulosa cells (GCs) from chicken follicles. In total, 600 Lohmann commercial laying hens, aged 64 weeks, were randomly assigned to four treatment groups: a control group, a theaflavin-supplemented group, an oxidized corn gluten meal group, and a combination group. After 8 weeks of feeding, production performance, egg quality, and antioxidant status, along with GC apoptosis and the antioxidant capacity of eggs, were measured. The results demonstrated that oxidized corn gluten meal significantly reduced production performance, antioxidant capacity, and egg quality in laying hens while increasing GC apoptosis. Theaflavin significantly enhanced egg production during weeks 5–8, along with superoxide dismutase activity in the liver, serum, and ovary, alongside egg white reducing power and egg yolk threonine content (p < 0.05). Additionally, theaflavin decreased feed conversion ratios during weeks 5–8 and 1–8, lowered egg white malondialdehyde content (p < 0.05), and inhibited GC apoptosis. In conclusion, oxidized protein reduced production performance, while theaflavin supplementation partially alleviated its adverse effects.